2016
DOI: 10.1002/cam4.641
|View full text |Cite
|
Sign up to set email alerts
|

The Barrett‐associated variants at GDF7 and TBX5 also increase esophageal adenocarcinoma risk

Abstract: Barrett's esophagus (BE) and esophageal adenocarcinoma (EAC) represent two stages within the esophagitis‐metaplasia‐dysplasia‐adenocarcinoma sequence. Previously genetic risk factors have been identified that confer risk to BE and EAC development. However, to which extent the genetic variants confer risk to different stages of the BE/EAC sequence remains mainly unknown. In this study we analyzed three most recently identified BE variants at the genes GDF7 (rs3072), TBX5 (rs2701108), and ALDH1A2 (rs3784262) sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…We found that both GDF6 and GDF7 were downregulated in CRC tissues. While we could find no earlier documentation of these genes having an association with CRC risk, GDF7 is a ligand in the BMP pathway that has been shown to regulate the Hedgehog and Wnt pathways and has been associated with the pro-inflammatory phenotypes in many diseases including Barrett’s Esophagus [ 49 ] and esophageal adenocarcinoma [ 50 ]. Additionally, the role of Wnt in CRC has been established [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that both GDF6 and GDF7 were downregulated in CRC tissues. While we could find no earlier documentation of these genes having an association with CRC risk, GDF7 is a ligand in the BMP pathway that has been shown to regulate the Hedgehog and Wnt pathways and has been associated with the pro-inflammatory phenotypes in many diseases including Barrett’s Esophagus [ 49 ] and esophageal adenocarcinoma [ 50 ]. Additionally, the role of Wnt in CRC has been established [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] Many of these associations have been replicated in subsequent studies. 40,41 One of the largest initiatives has pooled analyses of all GWAS studies published until February 2016, comprising 6167 cases of BE, 4112 cases of EAC, and 17,159 controls. 42 These confirmed associations for all 8 previously identified SNPs, along with 8 new risk loci; 2 of these are linked to genes that regulate body fat.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Despite enormous efforts in treating the disease, including surgeries, radiation therapy, and chemotherapy, the 5‐year survival rate of oesophageal cancer has not improved significantly . Increased evidence has shown that development of oesophageal cancer is correlated with abnormal gene activity . However, the molecular mechanisms underlying the regulation of the aberrant genes in oesophageal cancer remain to be further tested for gene correction strategies.…”
Section: Introductionmentioning
confidence: 99%